Differentiated mitochondrial function in mouse 3T3 fibroblasts and human epithelial or endothelial cells in response to chemical exposure. Issue 2 (25th September 2018) - Boncler, Magdalena; Lukasiak, Magdalena; Dastych, Jaroslaw; Golanski, Jacek; Watala, Cezary
Abstract: Mouse 3T3 fibroblasts are commonly used for in vitro toxicity testing; however, their sensitivity to stimuli is not well defined. To assess the sensitivity of the 3T3 cell line, the study compared the changes in mitochondrial membrane potential (MMP) occurring after exposure to eight chemicals known to demonstrate pro‐apoptotic activity (glycerol, isopropanol, ethanol, paracetamol, propranolol, cobalt chloride, formaldehyde and atropine). Five cell lines were used as follows: mouse 3T3 fibroblasts, human epithelial cells (A549, Caco‐2 and HepG2) and human endothelial cells (HMEC‐1). Cell sensitivity was assessed based on the total area under and over the dose‐response curves (AUOC) in relation to baselines. The 3T3 fibroblasts had the highest AUOC values and were the most sensitive to the action of all the examined chemicals, with the exception of formaldehyde. Significant changes in MMP between the 3T3 cell line and other cells were observed after cell treatment with atropine (A549, Caco‐2 or HMEC‐1 cells vs 3T3 cells, P  < 0.05), propranolol (A549 vs 3T3 cells, P  < 0.01; HepG2 vs 3T3 cells, P  < 0.05), cobalt chloride (A549 cells vs 3T3 cells, P  < 0.01) or ethanol (HMEC‐1 vs 3T3, P  < 0.05). Formaldehyde appeared the most toxic compound for Caco‐2 cells (Caco‐2 vs 3T3 cells, P  < 0.05). The surface areas (AUOC) calculated for each other chemical and obtained for HepG2, Caco‐2, A549 and HMEC‐1 did not differ significantly between cell lines. We postulate that mouse 3T3 fibroblasts demonstrate significantly higher relative sensitivity to many agents with toxic potential.